Trends in the Evolution of Insect Parasitism by Nematodes as Inferred from Fossil Evidence - Poinar, George (Society of Nematologists, 2003)
Fossil evidence can reveal a wealth of information regarding entomogenous nematodes. Amber is an excellent medium for the preservation of such fossils because it protects delicate organisms like nematodes, often along with their insect hosts. Such fossils establish a baseline for the appearance and continuation of parasite lineages as well as parasite-host associations. Thus far, fossil records of insect parasites have been discovered in the following nematode groups: terrestrial and aquatic Mermithidae, Tetradonematidae, Iotonchidae, Diplogasteridae, Allantonematidae, Sphaerulariidae, and Rhabditidae. Records date from 15 to 130 million years, demonstrating that these associations have existed for a considerable length of time.